Applying Syntax Bootstrapping to Facilitate Early Language Skills in Children with Autism - Nur, Nur Lailiyah; Lestariningrum, Anik; Ratnawati, Vivi; Lusiana, Meyta; Putri, Farika Nuria (JURNAL PENDIDIKAN USIA DINI, 2026)
This study investigates the role of syntactic bootstrapping as a linguistic strategy to support language development in children with autism within inclusive elementary education settings. Syntactic bootstrapping refers to the process by which learners use syntactic cues to infer the structure and meaning of utterances. Employing a qualitative case study design, the research involved classroom observations, in-depth interviews with teachers, and document analysis of autistic students in an inclusive school context. The findings reveal that syntactic bootstrapping strategies, when systematically adapted to the cognitive and linguistic profiles of children with autism, enhance their ability to comprehend sentence structures and improve both receptive and expressive language skills. Specifically, structured exposure to patterned sentences and guided interaction with syntactic cues were found to facilitate more accurate interpretation and production of utterances. The study offers several practical implications. First, it highlights the need for teachers to integrate syntax-focused scaffolding techniques into daily instruction, such as explicit modeling of sentence structures and repetition of patterned input. Second, it suggests the development of instructional materials that emphasize consistent and meaningful syntactic patterns. Third, at the policy level, the findings support the inclusion of linguistically-informed intervention strategies in teacher training programs and inclusive education guidelines to ensure more equitable learning opportunities for children with autism.